- Profil Fitokimia dan Evaluasi Nutrisi Kultivar Kacang Tunggak Indigenus (Vigna unguiculata L.) dari Bulukumba, Sulawesi Selatan, Indonesia - Arifuddin, Widiastini; Al Banna, Maisya Zahra (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Cowpea (Vigna unguiculata L.) is a leguminous crop recognized for its high nutrient density and substantial potential as a functional food. Bulukumba Regency in South Sulawesi, Indonesia, harbors two locally adapted red and white cultivars that have been traditionally cultivated and consumed as staple foods. This study aimed to evaluate their nutritional composition, antioxidant capacity, and bioactive compound profiles. Proximate composition was determined following the AOAC protocols, tannin content was quantified using a modified vanillin–HCl assay, antioxidant activity was assessed via the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, and bioactive compounds were identified through Gas Chromatography–Mass Spectrometry (GC–MS). Both cultivars exhibited high protein (20.47–21.03%) and carbohydrate (43.93–51.91%) contents, low lipid content (0.63%), and comparable ash content (3.25–3.28%). Tannin content was substantially higher in the red cowpea (465.61 µg/g) than in the white cowpea (130.43 µg/g). Antioxidant activity was significantly greater in the red cultivar (2,115.33 µg/g) compared with the white cultivar (507.18 µg/g). GC–MS analysis revealed a diverse range of bioactive compounds, including fatty acids (oleic, palmitic, and pentadecanoic acids), alcohols, esters, nitrogen-containing molecules, vitamins, terpenoids, and phenolics—many of which are reported to possess antioxidant, antimicrobial, anti-inflammatory, anticancer, and cardioprotective properties. These findings highlight the superior functional potential of the red cultivar and support the valorization of local cowpea germplasm for improved nutrition, human health, and sustainable agricultural development.